2014
DOI: 10.1016/j.bbamem.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Guanidino groups greatly enhance the action of antimicrobial peptidomimetics against bacterial cytoplasmic membranes

Abstract: A promising class of potential new antibiotics are the antimicrobial peptides or their synthetic mimics. Herein we assess the effect of the type of cationic side chain (i.e., guanidino vs. amino groups) on the membrane perturbing mechanism of antimicrobial α-peptide–β-peptoid chimeras. Two separate Langmuir monolayers composed of 1,2-dipalmitoyl-sn-glycero-3-phosphatidylglycerol (DPPG) and lipopolysaccharide Kdo2-lipid A were applied to model the outer membranes of Gram-positive and Gram-negative bacteria, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 85 publications
4
61
0
Order By: Relevance
“…Recent work from our lab showed increased antimicrobial activity of the BF2 and DesHDAP1 variants (BF2R and DesHDAP1R) where all cationic residues were replaced with arginine [24]. Similar results have been observed for other systems, particularly in the design of antimicrobial peptidomimetics [4348]. While arginine residues can also increase membrane interactions, our results here show that the enhanced activity of arginine containing peptides may also be due to their increased ability to target nucleic acids.…”
Section: Discussionsupporting
confidence: 86%
“…Recent work from our lab showed increased antimicrobial activity of the BF2 and DesHDAP1 variants (BF2R and DesHDAP1R) where all cationic residues were replaced with arginine [24]. Similar results have been observed for other systems, particularly in the design of antimicrobial peptidomimetics [4348]. While arginine residues can also increase membrane interactions, our results here show that the enhanced activity of arginine containing peptides may also be due to their increased ability to target nucleic acids.…”
Section: Discussionsupporting
confidence: 86%
“…Though the two residues have the same net charge, switching the guanidinium groups of arginine for the amine groups of lysine has been shown to decrease the antimicrobial activity, membrane disruptive ability, and cytotoxicity for many AMPs [8, 9, 7, 10], including tritrpticin [11, 6], human neutrophil peptide 1 [12], and KR-12 [13]. Likewise, synthetic peptidomimetics containing amine side chains were shown to be less active against eight bacterial strains than those containing guanidinium groups and, unlike their guanidinium-containing counterparts, do not disrupt DPPG monolayers [14]. Studies comparing arginine and lysine oligomers have shown that polyarginine enters cells far more efficiently than polylysine [15], and binds more strongly to both POPC and mixed POPC/POPG bilayers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Initially invented by Olsen et al ., this biomimetic framework represents AMP with incorporated N ‐alkyl‐β‐alanine (β‐peptoid) residues (Figure ) . Considering in vitro activities of lysine‐containing chimeras to be highly sensitive toward the overall cationicity, as well as the charge distribution, compounds with lysine‐to‐homoarginine (Lys‐to‐ h Arg) substitution have been designed and their interactions with DPPG and Kdo 2 ‐lipid A monolayers have been probed . The working hypothesis was the guanidine groups of h Arg allow for a stable electrostatic binding to the lipid polar moieties by displacing bivalent cations.…”
Section: X‐ray‐guided Design and Optimization Of Bioactive Peptoidsmentioning
confidence: 99%
“…Using phosphatidylcholine vesicles as a membrane model, it has been shown that peptide‐peptoid chimeras prevent lateral diffusion of lipids in fluid phase by interacting with their head groups . However, GIXD data suggest the involvement of hydrocarbon chains in their mechanism of action against negatively charged DPPG . It needs to be noted that lipid head groups may also affect the molecular packing.…”
Section: X‐ray‐guided Design and Optimization Of Bioactive Peptoidsmentioning
confidence: 99%